N'-(phenyl-pyridin-2-yl-methylene)-hydrazine carbodithioic acid methyl ester enhances radiation-induced cell death by targeting Bcl-2 against human lung carcinoma cells - Park, JK; Chung, YM; Kim, BG; Yoo, YA; Yang, BS; Kim, JS; Yoo, YD (AMER ASSOC CANCER RESEARCH, 2004)
To develop a new radiosensitizer, we screened a chemical library and selected one chemical reagent, N'-(phenyl-pyridin-2-yl-methylene)-hydrazine carbodithioic acid methyl ester (PHCM), which was already known to have antifungal and antimicrobial properties. PHCM enhanced radiation-induced cell death and its mean calculated dose enhancement ratio was 1.17. PHCM was found to induce the phosphorylation of p38 mitogen-activated protein kinase, and combined treatment with PHCM and radiation down-regulated Bcl-2. In a xenograft assay, the combined PHCM and radiation group showed 39.3 days of growth delay versus the control in terms of tumor growth. The enhancement factor of this combined treatment was determined to be 4.02.
Keywords: CANCER-CELLS; IONIZING-RADIATION; INDUCED APOPTOSIS; P53; KINASE; ACTIVATION; INVOLVEMENT; WORTMANNIN; INHIBITION; RESISTANCE